Wprowadzenie alternatywnych i wspomagających metod komunikacji u dziecka z mózgowym porażeniem dziecięcym - Gryszka-Mędrek, Zuzanna (Logopedia Silesiana, 2012)
The introduction of Alternative and Facilitating Methods of Communication ofa child suffering from cerebral palsy This article brings up the issue of communication difficulties for people with various disabilities. In the theoretical part it widely explains the rise and development of alternative and supportive methods of communication, and it describes various forms of non-verbal means of communicating. The second part of this article constitutes a case study of a thirteen-year-old mute girl who was taught communicating with application of non-verbal methods, and it also includes a short description of the methods used in working with the child. The course of therapeutic action is to be found in “The Supporting Materials, Didactic Visual aids and Reports” Logopedii Silesiany part.